Kajian Literatur: Pengaruh Penambahan Hati Ayam terhadap Kandungan Zat Besi pada Produk Formulasi Makanan untuk Mencegah Anemia - Hafizotun Tsaqifah; Tasya Shafa Salsabila Muda; Dhiyah Ariba Oktaviani; Annis Catur Adi (Universitas Airlangga, 2024)
Backgound: Iron (Fe) together with protein is needed by the body in the formation of hemoglobin so that if the amount of intake is less, the number of red blood cells used to transport oxygen to the lungs is not enough to meet the physiological needs of the body with normal hemoglobin levels of 12-15 g/dl in female adolescents and 13-17 g/dl in male adolescents. Iron deficiency causes disturbances or obstacles to growth which can cause symptoms of lethargy, weakness, fatigue and forgetfulness to anemia. Chicken liver is the most common source of iron used as a food formulation additive because it is easily accessible and is a source of heme iron which is more easily absorbed and contains less mineral binding material. Therefore, nutrient fortification in food formulations by utilizing chicken liver is needed to prevent anemia. Objectives: The effect of iron nutrient levels from the results of food formulations was analyzed by utilizing chicken liver as a substitute material intended to increase iron intake in an effort to prevent anemia. Methods: This research used the Literature Review method by tracing and reviewing several similar research articles that used experimental studies, especially in terms of product development that utilized chicken liver as a source of iron intake. The article search used the Google Scholar electronic database within the last 10 years (2014-2024) with keywords “anemia”,